Time preference and the process of civilization. Issue 4 (11th April 2016) - Howden, David; Kampe, Joakim
Abstract : Purpose: – The authors begin with an admittedly simplistic statement: "civilization" is best represented by the increased availability of utility providing goods and services. In other words, civilization is synonymous with economic development. The purpose of this paper is to concern three questions. First, how does civilization develop? Second, what is time preference and how does it affect the development of civilization, or what the authors call the "process of civilization." Third, what factors affect time preference, and how do changes in time preference affect this civilizing process? Through these three questions, the authors provide the theoretical answer to why civilization developed, instead of the more common historical how civilization actually developed. Design/methodology/approach: – The authors survey a variety of theories of civilization, and then develop an alternative that answers the question of "how civilization develops" rather than the more common "how did civilization develop." Findings: – Endogenous reductions in time preference are determined to be the best explanation of the spark that instigates the process of civilization. It also allows for other approaches to fall under its umbrella, thus providing one general theory in place of the current-specific theories. Originality/value: – The value lies in the creation of a general theory of civilization, against which other theories looking at specific factors can be gauged.